2016
DOI: 10.1007/978-1-4939-3539-0_20
|View full text |Cite
|
Sign up to set email alerts
|

Assay of Endocannabinoid Uptake

Abstract: Endocannabinoids at physiological concentrations are crossing cellular membranes by facilitated diffusion, a process that can be studied by measuring transport kinetics. Here, we describe a radiosubstrate-based assay using arachidonoyl[1-(3)H]ethanolamine or arachidonoyl[1,2,3-(3)H]glycerol to measure the cellular endocannabinoid uptake in a three-phase assay with human U937 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Next, we assessed whether pharmacologically inhibitable AEA uptake by the putative EMT (Chicca et al, 2012;Nicolussi and Gertsch, 2015) was observable in these cells. By monitoring the uptake of radiolabeled [ 3 H]AEA by the cells, we found that acute inhibition (15 minutes, 10 mmol/L) of AEA cellular uptake using the reference eCB transport inhibitor UCM707 (Ló pez-Rodríguez et al, 2003;Rau et al, 2016) was able to significantly alter the eCB uptake process. UCM707 reduced the intracellular [ 3 H]AEA signal, which was accompanied by a significant increase in extracellular [ 3 H]AEA levels compared with vehicle control.…”
Section: Sebocytes Exhibit a Pharmacologically Inhibitable Ecb Uptakementioning
confidence: 96%
“…Next, we assessed whether pharmacologically inhibitable AEA uptake by the putative EMT (Chicca et al, 2012;Nicolussi and Gertsch, 2015) was observable in these cells. By monitoring the uptake of radiolabeled [ 3 H]AEA by the cells, we found that acute inhibition (15 minutes, 10 mmol/L) of AEA cellular uptake using the reference eCB transport inhibitor UCM707 (Ló pez-Rodríguez et al, 2003;Rau et al, 2016) was able to significantly alter the eCB uptake process. UCM707 reduced the intracellular [ 3 H]AEA signal, which was accompanied by a significant increase in extracellular [ 3 H]AEA levels compared with vehicle control.…”
Section: Sebocytes Exhibit a Pharmacologically Inhibitable Ecb Uptakementioning
confidence: 96%
“…Among these, facilitated diffusion is influenced by both the interaction of eCBs with extra-and intracellular binding proteins and their metabolic enzymes. The measurement of facilitated diffusion and plasma membrane lipid transport is challenging and demands special phenotypic assays not easily accessible for routine screening Fowler, 2013;Rau et al, 2016;Reynoso-Moreno et al, 2023). A major challenge has been to differentiate FAAH and AEA uptake inhibitors as these processes are intrinsically coupled (Fowler et al, 2004;Vandevoorde and Fowler, 2005;Hillard et al, 2007).…”
Section: Therapeutic Potential Of Monoacylglycerol Lipase (Magl)mentioning
confidence: 99%